WORKSHOP ON INCREASING CARDIOVASCULAR ENDURANCE AND CONCENTRATION THROUGH LOW-IMPACT LOW IMPACT AEROBIC DANCE - Arfanda, Poppy Elisano; Ians Aprilo,; Arimbi, Arimbi; M. Adam Mappompo,; Nurliani, Nurliani; Wahyana Mujari Wahid, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The main problem is the decreased level of fitness and concentration. The reason is technological advances so that a person does not need the energy to carry out his activities and can be recorded and stored in an online database. The author provides a community service solution with low-impact aerobic dance to increase cardiovascular endurance and concentration in 36 female students aged 18-20 years. The pretest at the first meeting, low-impact aerobic dance material is 30 minutes long, 3 times per week is carried out for 6 weeks, and ends with a posttest. The pretest and posttests used the Multi-Stage 20m Shuttle Run Fitness Test for cardiovascular endurance and the Grid Concentration Test for concentration. There was an average increase in cardiovascular endurance of 3.34 and concentration of 2.11. This dedication is necessary for increasing cardiovascular endurance and concentration so that daily activities do not experience fatigue and still have energy reserves to carry out other activities and be more focused.